Doomscrolling as Cyberloafing in the Workplace: A Systematic Literature Review - Vecco Suryahadi Saputro; Larasati Puspa Martani Sugianto; Saskia Salmana Dahyar; Adisti Gilang Cempaka; Said Aryonindito (Universitas Nusa Cendana, 2026)
Introduction Doomscrolling represents a harmful form of digital behavior that must be identified and mitigated. However, the literature on doomscrolling remains fragmented across multiple disciplines. Aim Exploration of the primary determinant factors of doomscrolling behaviors, their impact on employees, and suggested internal controls to mitigate the behavior, through Systematic literature reviews using PRISMA Guidelines. Result The findings reveal that coping mechanisms and FOMO (Fear of Missing Out) are the most significant factors of cyberloafing and doomscrolling behavior. The findings demonstrate that while doomscrolling leads to detrimental outcomes such as task avoidance and deprioritization of responsibilities, they concurrently serve as a coping mechanism. Employees frequently resort to digital escapism, such as browsing e-commerce platforms or consuming humorous content, to release stress. Conclusion Ineffective procedures and a lack of workload fairness may cause employees to engage in mischief behavior. For organizations, it is important to implement control mechanisms to reduce deviant behavior.